Identificação dos coralitos de pólipos fundadores de corais recifais do Brasil (Cnidaria, Anthozoa, Scleractinia) - Calderon, Emiliano Nicolas (2003)
To study an organism's life history, it is important to identify them throughout their life cycle. ln corals, a complicating factor is the difficulty of identification at their initial stages. The taxonomy of corais is based on skeletal structures present in the adults. The purpose of this study was to describe the juveniles of Brazilian reef corals and critically analyze the taxonomic important skeletal characteristics at different developmental stages. Recruitment plates from Banco de Abrolhos, Itacolomis Reefs and Arraial do Cabo, were examined. Eight taxa, up to one year of age, were identified from family to species. Results show that recruitment identification depends on the corallum, its skeletogenesis, and the structures that define each taxa. This study demonstrates that it is possible to classify juvenile corals, although the process of identification can be demanding, requiring an extensive knowledge of the structures involved in the identification. Juvenile identification is important for life history and recruitment studies, as well as, the estimation of growth and maintenance of coral populations. The identification of recruits is an important tool for the optimization of management, conservation, and recovery of reef corals.